A Systematic Study on the Effects of Solvating Solvents and Additives in Localized High‐Concentration Electrolytes over Electrochemical Performance of Lithium‐Ion Batteries. Issue 17 (20th March 2023) - Jia, Hao; Kim, Ju‐Myung; Gao, Peiyuan; Xu, Yaobin; Engelhard, Mark H.; Matthews, Bethany E.; Wang, Chongmin; Xu, Wu
Abstract: Localized high‐concentration electrolytes (LHCEs) based on five different types of solvents were systematically studied and compared in lithium (Li)‐ion batteries (LIBs). The unique solvation structure of LHCEs promotes the participation of Li salt in forming solid electrolyte interphase (SEI) on graphite (Gr) anode, which enables solvents previously considered incompatible with Gr to achieve reversible lithiation/delithiation. However, the long cyclability of LIBs is still subject to the intrinsic properties of the solvent species in LHCEs. Such issue can be readily resolved by introducing a small amount of additive into LHCEs. The synergetic decompositions of Li salt, solvating solvent and additive yield effective SEIs and cathode electrolyte interphases (CEIs) in most of the studied LHCEs. This study reveals that both the structure and the composition of solvation sheaths in LHCEs have significant effect on SEI and CEI, and consequently, the cycle life of energetically dense LIBs. Abstract : The effects of microscopic solvation structure, solvating solvent and additive of localized high‐concentration electrolytes (LHCEs) over the electrolyte properties, the electrode/electrolyte interphases and the cycling stability of lithium‐ion batteries (LIBs) were systematically studied. The synergetic decomposition of anion, proper solvent and additive in LHCEs is the key to forming effective interphases and achieving long cycle life of LIBs.